Happy Valley - Series 2 Episode 1-6 - Wainwright, Sally; Wainwright, Sally; Hardiman, Neasa; Strasburg, Ivan; McDonnell, Andrew; O'Donnell, Andrew; Lancashire, Sarah; Finneran, Siobhan; Norton, James; Doyle, Kevin (BBC, 2016)
Sarah Lancashire returns in the acclaimed BBC thriller written by Sally Wainwright. No-nonsense police sergeant Catherine Cawood is back heading up her team of dedicated police officers in the Calder Valley in West Yorkshire. While on duty, she makes a gruesome discovery - a body. The victim's injuries bear a striking similarity to a string of other murders over the previous few months, suggesting a serial killer is on the loose. But the case becomes even more shocking when it emerges that Catherine knows the victim - something that could have serious repercussions for both herself and her family. [Cover]
Keywords: Blu-Ray-Disc